1992
DOI: 10.1111/j.1600-0404.1992.tb05069.x
|View full text |Cite
|
Sign up to set email alerts
|

IgM M-protein in a patient with sensory-dominant neuropathy binds preferentially to polysialogangliosides

Abstract: A 77-year-old man presented sensory-dominant neuropathy associated with IgM M-protein reacting with various gangliosides. The M-protein bound to gangliosides with polysialosyl residue, such as GD1b, GD3, GT1b, GT3, GQ1b, and GQ1c. In addition, GD1a, GM3 and LM1, having a terminal monosialosyl epitope, were also recognized. Previously, Ilyas et al. described a similar case in which sensory symptoms were associated with IgM M-protein reacting with gangliosides containing a disialosyl group, such as GD3, GD1b, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…In all the previously reported cases of chronic sensory ataxic IgM paraproteinaemic neuropathy [1-5, 9, 12, 13], the antibodies reacted with disialylated gangliosides. However, some sera also reacted with GD1a, GM3 and LM1 -gangliosides which lack disialosyl epitopes and share a NeuNAc(α2-3)Gal terminal epitope -in addition to GT1b and other gangliosides containing disialosyl groups [2,6,9,10]. Different epitopes have been proposed to explain these findings.…”
Section: Ricard Rojas-garcia Eduard Gallardo Monica Povedano Noemi Dementioning
confidence: 86%
“…In all the previously reported cases of chronic sensory ataxic IgM paraproteinaemic neuropathy [1-5, 9, 12, 13], the antibodies reacted with disialylated gangliosides. However, some sera also reacted with GD1a, GM3 and LM1 -gangliosides which lack disialosyl epitopes and share a NeuNAc(α2-3)Gal terminal epitope -in addition to GT1b and other gangliosides containing disialosyl groups [2,6,9,10]. Different epitopes have been proposed to explain these findings.…”
Section: Ricard Rojas-garcia Eduard Gallardo Monica Povedano Noemi Dementioning
confidence: 86%
“…Bulbar dysfunction may also be present in chronic sensory ataxic neuropathy with anti-disialosyl IgM antibodies 7. A review of previously reported cases with chronic ataxic neuropathy has shown that sera from some patients had antibodies against GD1a and GM3 in addition to reactivity against disialylated gangliosides including GT1b 6 10 11. Furthermore, in the largest series of 18 patients with chronic sensory ataxic neuropathy reported by Willison et al ,7 five sera showed this pattern of antiganglioside reactivity.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, no cases of CANOMAD associated with glomerulonephritis have been described. Several cases of an association between extramembranous glomerulonephritis and acute or chronic forms of polyradiculoneuropathy5, 15, 17 or chronic demyelinating neuropathy16, 24 have been reported, however. Concomitant regression of glomerulonephritis and polyneuropathy and delayed resolution of the nephropathy were both reported in these cases.…”
Section: Discussionmentioning
confidence: 99%